A Novel Center-Tapped Rectifier With Current-Balancing and Voltage-Clamped Capability for LLC Resonant Converter - Keon-Woo Kim; Moon-Young Kim; Jeong-Il Kang (IEEE Access, 2024)
A novel center-tapped rectifier with current-balancing and voltage-clamped (CBVC) capability for the LLC resonant converter is proposed. A secondary capacitor is inserted between the contact points of the rectifier diode and the secondary winding of the transformer. The amount of the current flowing through each primary switches and rectifier diodes become almost the same by adopting the CBVC center-tapped rectifier. Equal distribution of the current improves the reliability and lifetime of the primary switches and rectifier diodes. In addition, the voltage across the rectifier diodes in the CBVC center-tapped rectifier is clamped by two times the output voltage. The conduction loss of the rectifier diodes is decreased since the diodes with low forward voltage drop can be used. Moreover, half of the output capacitor is utilized as a secondary side capacitor, which means no additional components. The validity of the proposed converter is verified through experiments on a prototype for 400 VDC input to 45–70 V/4 A output application.